Anthony Collins on the Status of Consciousness - Lähteenmäki, Vili (Vivarium, 2014)
Anthony Collins (1676-1729) maintains that consciousness might be a material process or result from material processes. On the one hand, Collins accepts Locke’s view that from consciousness, i.e., the activity of thinking, we acquire no knowledge about the nature of the thinking substance. On the other, he takes seriously Samuel Clarke’s challenge that the thinking substance must be suitably unified because consciousness is unified. In this paper, I argue that, throughout his correspondence with Clarke, Collins maintains that consciousness signifies actual thinking and does not refer to the capacity of thinking. His main materialist thesis is that the powers of parts of material systems can bring about unified powers and that the power of thinking may be such a power. Collins attempts to satisfy the unity requirement by arguing that a unity correspondence can obtain between consciousness and the power of thinking that is realized in a material composite.